Political-Legal Order and the Curious Double Character of China's Courts. Issue 1 (4th March 2019) - LI, Ling
Abstract: This article provides an analytical account of how politics and law in China are organically integrated in the institutional architecture of courts as designed by the Chinese Communist Party ("the Party"). This design allows the Party to retain its supreme authority in the interpretation, application, and enforcement of the law through its institutional control over courts. At the same time, the Party can, under this design, also afford to grant an autonomous sphere where courts can perform their adjudicative functions with minimal interference from the Party, as long as the Party is assured of full authority to determine the scope of the "autonomous-zone, " to impose rules on it, and to revoke it when necessary. Consequently, courts assume a double character: a pliant political agent on the one hand and a legal institution of its own agency on the other.